THE EFFECT OF INFORMATION TECHNOLOGY BASED FLIPPED CLASSROOM LEARNING MODEL ON THE CREATIVITY AND LEARNING OUTCOMES OF CIVIC EDUCATION AT GRADE IV OF SDN BLIGO - Ninik Fatmawati; Yatim Riyanto; Rr Nanik Setyowati (Jurnal PAJAR (Pendidikan dan Pengajaran), 2021)
This study aimed to determine the effect of information technology-based flipped classroom learning model on creativity and learning outcomes for grade four Civics at SDN Bligo. This research was an experimental research with a pretest posttest control group design. The subjects of this study were fourth grade students of SDN Bligo Sidoarjo. Data collection techniques were conducted through creativity tests and learning outcomes tests. Furthermore, the data were tested using validity and reliability tests, while the learning tools were tested through expert validation. The requirements of data analysis included normality tests and homogeneity tests. The analytical technique used was the t-test, which was carried out twice: first to determine the initial conditions (pretest) of the experimental and control groups, and second to determine the condition after being given treatment (posttest). The results showed that (1) there was an effect of the information technology-based flipped classroom learning model on students’ creativity in Civics education at the fourth grade of elementary school, and (2) there was an effect of the information technology-based flipped classroom learning model on students’ learning outcomes in Civics education at the fourth grade of elementary school. In short, this learning model could be used as a solution for learning from home or online learning implemented due to the impact of the COVID-19 pandemic.